2019
DOI: 10.1002/jee.20264
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the interplay of cognitive and metacognitive knowledge in computational modeling and simulation practices

Abstract: Background Modeling and simulation practices have become commonplace in modern engineering, but in‐depth research on the development of modeling and simulation expertise is needed to identify the learning processes involved in successfully acquiring these skills. Purpose This study investigated student dimensions of expertise when engaged in modeling and simulation practices. The guiding research question was “How do students use cognitive and metacognitive knowledge when engaged with computational modeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The models and modeling perspective has been heavily studied concerning engineering education [7,8,33]. Discipline-based modeling and simulation has been shown to help students build both programming skills and disciplinary skills within engineering contexts [24,28,31] Thus, bringing this perspective to incorporating computational thinking within education engineering contexts may give key insights into how best to create computational thinking-enabled engineering professionals.…”
Section: Implications For the Field Of Engineering Educationmentioning
confidence: 99%
“…The models and modeling perspective has been heavily studied concerning engineering education [7,8,33]. Discipline-based modeling and simulation has been shown to help students build both programming skills and disciplinary skills within engineering contexts [24,28,31] Thus, bringing this perspective to incorporating computational thinking within education engineering contexts may give key insights into how best to create computational thinking-enabled engineering professionals.…”
Section: Implications For the Field Of Engineering Educationmentioning
confidence: 99%
“…Qualitative analysis of the students' problem-solving process as described in the interviews resulted in an outcome space of four predominant archetypes of behavior. Findings from our study identified four categories of description; two for the cognitive dimension and two for the metacognitive dimension (Magana, Fennell, Vieira, & Falk, 2019). To summarize briefly, in the cognitive dimension, the two main approaches that students adopted were implementation-oriented and knowledge-oriented.…”
Section: Learning Strategiesmentioning
confidence: 87%
“…Drawing from Magana et al (2019), who also used thematic analysis within a phenomenological methodological framework (see also Daly et al, 2012), our analysis consists of the following steps: (1) use thematic analysis to construct a limited number of qualitatively different themes that describe the ways students experience school that lead to rote or to conceptual learning operations; (2) identify the central aspects of these themes including their frequency and affect;…”
Section: Discussionmentioning
confidence: 99%